Review for Analytical Methods for the Determination of Sodium Cephalothin - Rugani, Karen de Souza [UNESP]; Kogawa, Ana Carolina [UNESP]; Salgado, Hérida Regina Nunes [UNESP] (Taylor & Francis, 2019)
Infections are the second leading cause of global morbidity and mortality, therefore it is highly important to study the antimicrobial agents such as cephalosporins. Cephalothin, an antimicrobial agent that belongs to the class of cephalosporins, has bactericidal activity and it is widely used in the Brazilian health system. In literature, some analytical methods are found for the identification and quantification of this drug, which are essential for its quality control, which ensures maintaining the product characteristics, therapeutic efficacy and patient’s safety. The aim of this article is to review the available information on analytical methods for cephalothin. Thus, this study presents a literature review on cephalothin and the analytical methods developed for the analysis of this drug in official and scientific papers. It is essential to note that most of the developed methods used toxic and hazardous solvents, which makes necessary industries and researchers choose to develop environmental-friendly techniques, which will contribute to the harmonization of science, human, and environmental health.
Keywords: Analytical methods; antibiotic; cephalosporin; quality control; review; sodium cephalothin; stability